2014
DOI: 10.1177/1460458213483613
|View full text |Cite
|
Sign up to set email alerts
|

Health-oriented electronic oral health record: Development and evaluation

Abstract: This study aims to develop and evaluate a new Health-oriented Electronic Oral Health Record that implements the health-oriented status and intervention index. The index takes the principles of holistic oral healthcare and applies them to the design and implementation of the Health-oriented Electronic Oral Health Record. We designed an experiment using focus groups and a consensus (Delphi process) method to develop a new health-oriented status and intervention index and graphical user interface. A comparative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…However, a number of studies were able to leverage mobile networks and web-based platforms to wider benefit [24, 3538]. Studies reported different levels of maturity vis-à-vis EMR systems reach within a given context [27, 29, 3946]. However, studies conducted during earlier stages of EMR introduction documented progression from paper to electronic documentation as particularly time-consuming and requiring significant human resource allocation [21, 22, 47].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a number of studies were able to leverage mobile networks and web-based platforms to wider benefit [24, 3538]. Studies reported different levels of maturity vis-à-vis EMR systems reach within a given context [27, 29, 3946]. However, studies conducted during earlier stages of EMR introduction documented progression from paper to electronic documentation as particularly time-consuming and requiring significant human resource allocation [21, 22, 47].…”
Section: Resultsmentioning
confidence: 99%
“…Internal contextual factors were often couched within the larger, external context, but specifically related to an organisation's local access to ICT support [27, 47]; human resource needs in transitioning from paper to electronic records [23, 28, 31, 38]; local access to existing systems at higher levels, i.e., national/provincial/state infrastructure, web-based platforms [35, 39, 43, 45]; and locally existing (or lack of) EMR systems [29, 41, 45, 46, 4850].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall satisfaction for oral health index, treatment planning, and the ability to use oral health information system was measured. [ 12 ] The qualitative themes of this study could be considered for following evaluation phase of our project.…”
Section: Discussionmentioning
confidence: 99%